An algorithm for the management of Staphylococcus aureus carriage within patients with recurrent staphylococcal skin infections - Tzermpos, Fotios; Papadimas, Christos; Theologie-Lygidakis, Nadia; Kanni, Theodora; Tzanetakou, Vassiliki; Antonopoulou, Anastasia; Savva, Athina; Giamarellos-Bourboulis, Evangelos J. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2013)
Recurrent skin infections of staphylococcal origin raise the question of probable skin colonization by Staphylococcus aureus and the need for eradication. Available evidence does not exist for such settings. A management algorithm was developed by a group of experts that was implemented prospectively in 125 patients admitted for recurrent staphylococcal skin infections. Patients were tested for skin carriage of S. aureus in seven body surfaces. In the event of carriage, therapy was administered consisting of hair and body washing with antiseptics for 60 days and parallel oral treatment according to the antibiogram for 30 days. Patients were followed up for 3 years. Seventy-nine patients were colonized by S. aureus, 49 by methicillin-susceptible (MSSA) and 30 by methicillin-resistant (MRSA) isolates. The eradication rate following the algorithm was 83.7 % for patients colonized by MSSA and 90.0 % for patients colonized by MRSA. The greater eradication rates were achieved after treatment with one antistaphylococcal penicillin or clindamycin in the case of MSSA carriage and with clindamycin or a fluoroquinolone in the case of MRSA carriage. Of the 79 treated cases, 18 relapsed. Time to relapse did not differ between MSSA carriers and MRSA carriers. It is concluded that the suggested algorithm may be clinically efficacious and achieve high decolonization and low relapse within patients with recurrent staphylococcal skin infections colonized by either MSSA or MRSA.